Pengaruh Label Halal dan Inovasi Produk Terhadap Keputusan Pembelian Produk Es Teh Indonesia pada Mahasiswa Universitas Negeri Surabaya - Wafiqoh Nur Azizah Itsnatani; A’rasy Fahrullah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
In 2025, Indonesia is known as the country with the largest Muslim population in the world, with a percentage reaching 87.20% of its total population, thus driving an increase in demand for halal products, one of which is contemporary beverages that are popular among students. This study shows the need for beverage industry players to increase competitiveness through the application of halal labels with more creative product innovations. Research was also conducted to examine the influence of halal labels and product innovation on the purchasing decisions of Indonesian Iced Tea products among students at Surabaya State University. This study applied a quantitative approach with primary data sources through questionnaires. It involved 100 participants selected through purposive sampling criteria. The data was tested with multiple linear regression using IBM SPSS 25 software. The results of the study indicate that, halal labels have a positive and significant effect on personal purchasing decisions. These purchasing decisions are influenced by product innovation. In conclusion, halal awareness and the appeal of menu innovation are the main factors in student purchases. However, research on the influence of halal labels and product innovation on purchasing decisions for Es Teh Indonesia among students is still limited.